Aplikasi Model Inovasi Quintuple Helix untuk Strategi Pengendalian Pencemaran Air Sungai Brantas - Alfarizi, Muhammad; Ikhsan, Ridho Bramulya; Yuniarty, Yuniarty (Teknik Lingkungan Universitas Islam Indonesia, 2024)
The river is an inseparable part of the maritime concept because it is very close to people's lives, both those who live in cities and villages. Of the many rivers in Indonesia, the focus of this study is the Brantas River with the reason that the phenomenon of environmental cleanliness is not maintained. This study aims to explain the Quintuple Helix model according to public perception as input for the government, universities and business actors to work together to create sustainable innovations in water management in the Brantas River. This study uses a descriptive method with a survey approach. The results show the actual condition of water management in the Brantas River from the community's point of view based on the results of a survey at the Brantas River location seen from the Quintiple Helix Model, namely the education system, economic system, natural environment, media and culture-based society, and lastly is the political system. Until the conclusion, form a Quintuple Helix innovation model which will be a powerful strategy for controlling water pollution in the Brantas River